Поняття та значення парламентського контролю за законністю діяльності Державного бюро розслідувань в умовах воєнного стану в Україні : адміністративно-правові аспекти - Казанчук, І. Д.; Kazanchuk, I. D.; Казанчук Ірина Дмитрівна (Національні інтереси України. - 2024. - № 2. - С. 184-194, 2024)
Досліджено сутність та значення державного контролю за законністю діяльності Державного бюро розслідувань, а також окреслено особливості здійснення парламентського контролю за діяльністю ДБР України, як важливого виду зовнішнього державного контролю. Визначено напрямки удосконалення адміністративно-правового регулювання парламентського контролю за діяльністю Державного бюро розслідувань в умовах дії в України правового режиму воєнного стану.

The article is devoted to the study of the essence and significance of state control over the legality of the activities of the State Bureau of Investigation, as well as the outlined features of parliamentary control over the activities of the SBI of Ukraine, as an important type of external state control. Various scientific approaches to the definition of the terms «control», «state control» that take place in modern administrative and legal science are considered. Based on the analysis of scientific concepts and legal principles, a proper definition of the concept of «state control over the activities of the State Bureau of Investigation» is given. It should be understood as the activity of the authorized state authorities (their officials) regulated by the norms of the current legislation of Ukraine, which is expressed in the implementation of a set of surveillance actions in the form of checking the proper compliance by the employees of the DBR with the provisions of the Constitution of Ukraine, other legislative and by-laws of Ukraine, which regulate the activities of the SBI of Ukraine, identify and prevent violations of the current legislation, as well as provide assistance to the controlled structure in strengthening official discipline and maintaining the regime of legality in their activities. Attention is drawn to the fact that the supreme right to exercise state control over the legality of the activities of the State Bureau of Investigation of Ukraine belongs to the Verkhovna Rada of Ukraine as the only legislative body in the country. This type of control is called «parliamentary control». The legal status of the Commissioner of the Verkhovna Rada of Ukraine on human rights is considered separately, and his place in the system of control over the activities of the SBI of Ukraine is outlined. It is noted that the parliamentary control over the activities of the SBI is mainly legislative in nature, and does not extend to their operational investigative work, pretrial investigation. However, the peculiarity of control by the Verkhovna Rada of Ukraine is that this body, on the one hand, provides legal support for the functioning of the bodies of the SBI, and on the other hand, provides control over the observance and correct use of the norms of legislative acts adopted by it by all employees of the SBI in the field of law enforcement. The author concluded that state control over the activities of the SBI of Ukraine is an important function of managing the sphere of activity of the SBI, thereby ensuring the effective performance of the law enforcement function of the state by the employees of its structural units.

Исследованы сущность и значение государственного контроля за законностью деятельности Государственного бюро расследований, а также очерчены особенности осуществления парламентского контроля за деятельностью ГБР Украины как важного вида внешнего государственного контроля. Определены направления усовершенствования административно-правового регулирования парламентского контроля за деятельностью Государственного бюро расследований в условиях действия в Украине правового режима военного положения.
The concept and significance of parliamentary control over the legality of the activities of the State Bureau of Investigations during the conditions of marital state in Ukraine: administrative and legal aspects
Keywords: Державне бюро розслідувань; Україна; правове регулювання; контроль; державний контроль; Верховна Рада України; законність; State Bureau of Investigation; Ukraine; legal regulation; control; state control; Verkhovna Rada of Ukraine; legality; Государственное бюро расследований; Украина; правовое регулирование; государственный контроль; Верховная Рада Украины; законность